On directional subregularity of mappings. (2nd January 2023) - Burlică, Monica; Durea, Marius; Strugariu, Radu
Abstract : In this work we study directional regularities and subregularities of mappings with respect to fixed sets. We establish a result concerning the directional subregularity of compositions, and as consequence we deduce a directional variant of Lim's Lemma.